Neighbourhood socioeconomic status, maternal education and adverse birth outcomes among mothers living near highways. Issue 8 (11th July 2008) - Généreux, M; Auger, N; Goneau, M; Daniel, M
Abstract : Background: Residential proximity to highways is a potential proxy for exposure to traffic-related pollution that has been linked to adverse birth outcomes. We evaluated whether proximity to highway interacts with individual and neighbourhood socioeconomic status (SES) to influence birth outcomes. Methods: The study population consisted of all live singleton births in Montréal, Canada, from 1997 to 2001 (n = 99 819). Proximity was defined as residing within 200 m of a highway. Neighbourhood SES was measured for census tracts as the proportion of families below the low-income threshold. Individual SES was represented by maternal education. Using multilevel logistic regression, the odds of preterm birth (PTB), low birthweight (LBW) and small-for-gestational-age (SGA) birth were calculated for mothers residing in proximity to highways, accounting for individual and neighbourhood SES. Effect modification between SES and proximity to highway was tested for each outcome. Results: In wealthy neighbourhoods, proximity to highway was associated with an elevated odds of PTB (OR 1.58, 95% CI 1.23 to 2.04), LBW (OR 1.81, 95% CI 1.36 to 2.41) and SGA birth (OR 1.32, 95% CI 1.05 to 1.66). For highly educated mothers, proximity to highway was associated with PTB (OR 1.25, 95% CI 1.07 to 1.46) and LBW (OR 1.24, 95% CI 1.03 to 1.49), but the association was borderline for SGA birth (OR 1.15, 95% CI 1.00 to 1.32). Proximity to highway was not associated with birth outcomes in other maternal and neighbourhood SES categories. Conclusion: Counterintuitively, high SES mothers may be more likely than low SES mothers to experience adverse births associated with residential proximity to highway.